Optically Modulated Tunable O-Band Praseodymium-Doped Fluoride Fiber Laser Utilizing Multi-Walled Carbon Nanotube Saturable Absorber* - Ahmad, Harith; Ismail, Mohammad Faizal; Aidit, Siti Nabila (IOP Publishing, 2019)
A tunable and optically modulated fiber laser utilizing a multi-walled carbon nanotube based saturable absorber is demonstrated for operation in the O-band region. A praseodymium-doped fluoride fiber is used as the gain medium and the system is capable of generating modulated outputs at 1300 nm. Pulsed output is observed at pump powers of 511 mW and above, with repetition rates and pulse widths that can be tuned from 41 kHz and 3.4 μs to 48 kHz and 2.4 μs, respectively, at the maximum pump power available. A maximum average output power of 100 μW with a corresponding single pulse energy of 2.1 nJ is measured, while the tunability of the proposed laser is from 1290 nm to 1308 nm. The output is stable, with peak power fluctuations of ∼4 dB from the average value. © 2019 Chinese Physical Society and IOP Publishing Ltd.